Experimental Analysis of a Vibrating Feeder Prototype based on Electromagnets - Wong, Andrea Chu; Yagui, Ignacio Tokumura; Barrueto, Renato Miranda; Alegria, Elvis J. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
This article presents an experimental analysis of a prototype vibrating feeder actuated with two electromagnets. The initial approach is analytical, followed by mainly experimental investigations. Given that the system involves numerous unknown parameters and is susceptible to perturbations, conducting an experimental analysis becomes essential. The goal is to understand and identify the key design parameters that impact the conveyor’s performance. To achieve this, two electromagnets were selected as actuators, allowing for easy adjustment of different frequencies and amplitudes. The experiments were conducted multiple times to validate the results before thorough analysis. As an additional contribution, the CAD design details of the vibrating bowl prototype are provided, enabling replication for research purposes